2021
DOI: 10.1038/s41598-021-97065-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in physical activity during and after the first national lockdown due to the COVID-19 pandemic in England

Abstract: Recent studies have shown reduced physical activity at early stages of the COVID-19 pandemic. However, there is a lack of investigation on longitudinal changes in physical activity beyond lockdowns and stay-at-home orders. Moreover, it is unclear if there is heterogeneity in physical activity growth trajectories. This study aimed to explore longitudinal patterns of physical activity and factors associated with them. Data were from the UCL COVID-19 Social Study. The analytical sample consisted of 35,915 adults … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
90
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 61 publications
(59 reference statements)
13
90
3
1
Order By: Relevance
“…Smartphone-tracked PA data from the United Kingdom also indicated heterogeneous changes post-lockdown: while previously active people managed to increase their activity upon the lifting of the restrictions, moderately active people remained at their lockdown low [40]. The COVID-19 Social Study with 35,915 participants identified six different trajectories in the longitudinal change of PA [41]. Almost 30% of respondents reduced their activities, and 12% remained inactive over time [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smartphone-tracked PA data from the United Kingdom also indicated heterogeneous changes post-lockdown: while previously active people managed to increase their activity upon the lifting of the restrictions, moderately active people remained at their lockdown low [40]. The COVID-19 Social Study with 35,915 participants identified six different trajectories in the longitudinal change of PA [41]. Almost 30% of respondents reduced their activities, and 12% remained inactive over time [41].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 Social Study with 35,915 participants identified six different trajectories in the longitudinal change of PA [41]. Almost 30% of respondents reduced their activities, and 12% remained inactive over time [41]. Taken together, it seems plausible that at least some PA measures in certain population groups could have been reduced sustainably following the first lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is considered that a plan for each subject should be developed to increase their participation in moderate intensity physical activities. While a study reported that the changes in physical activity before and after COVID-19 are not affected by marital status [ 15 ], the type of family or cohabitant still needs to be considered as an effective factor to physical activity as the time spent on physical activity is 1.54 times more if one lives with a child than living alone [ 19 ]. Especially, efforts must be made to increase physical activity among those living alone or without a partner.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that physical activity (PA) has strong relevance for limiting and protecting human health during the pandemic [1]. However, physical distancing and self-isolation directives, implemented by many national governments to reduce the risk of person-to-person transmission of COVID-19, have been associated with decreased PA engagement [2,3]. During the initial COVID-19 containment (lockdown) period, PA decreased by more than 25% [3][4][5][6][7], whilst physical inactivity was associated with a higher risk for severe COVID-19 outcomes, including hospitalisations, admission to intensive care units and death [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, physical distancing and self-isolation directives, implemented by many national governments to reduce the risk of person-to-person transmission of COVID-19, have been associated with decreased PA engagement [2,3]. During the initial COVID-19 containment (lockdown) period, PA decreased by more than 25% [3][4][5][6][7], whilst physical inactivity was associated with a higher risk for severe COVID-19 outcomes, including hospitalisations, admission to intensive care units and death [8]. The University College London COVID-19 study demonstrated that a substantial proportion of their 35,915 adult sample showed persistent physical inactivity or decreasing PA during the first 22 weeks of the pandemic [3].…”
Section: Introductionmentioning
confidence: 99%